Landing quality in artistic gymnastics is related to landing symmetry - Cuk, I.; Marinsek, M. (Biology of Sport, 2013)
In gymnastics every exercise finishes with a landing. The quality of landing depends on subjective (e.g. biomechanical) and objective (e.g. mechanical characteristics of landing area) factors. The aim of our research was to determine which biomechanical (temporal, kinematic and dynamic) characteristics of landing best predict the quality of landing. Twelve male gymnasts performed a stretched forward and backward salto; also with 1/2, 1/1 and 3/2 turns. Stepwise multiple regression extracted five predictors which explained 51.5% of landing quality variance. All predictors were defining asymmetries between legs (velocities, angles). To avoid asymmetric landings, gymnasts need to develop enough height; they need higher angular momentum around the transverse and longitudinal axis and they need to better control angular velocity in the longitudinal axis.